Shock tube: activating and propagation conditions - Schuster, Jaroslav; Pelikán, Vojtěch; Matyáš, Robert (Univerzita Pardubice, 2020)
Paper describes measurement of the key parameters, which are necessary for the shock tube activation and stable propagation inside shock tube. These parameters are important for reliable functioning of shock tube. Shock tube is well known and established mainly for quarrying. However, the description of the propagation processes inside the shock tube is not fully understood yet. The work is focused on the measurement of pressure and pressure rate, which believed to be as key parameters. These parameters were measured under different conditions of activation or stable propagation. Firstly was measured stable propagation condition of the shock tube. Second condition was measurement of run distance. It is distance, which is needed to reach stable propagation. Last measured condition was inert gap. Results of inert gap measurement shown dependence of transmission probability to length of shock tube segment without fill. Results indicates basic pressure parameters, which are necessary for activation and stable shock propagation of the shock tube. These information are important for a thorough understanding of the propagation processes in the shock tube and increasing of reliability.
Rázová trubice: podmínky aktivace
Keywords: maximum pressure; pressure rate; shock tube; activation; propagation; maximální tlak; tlakový nárůst; rázová trubice; aktivace; šíření